Representing Cases for CBR in XML - Coyle, Lorcan; Hayes, Conor; Cunningham, Padraig (Trinity College Dublin, Department of Computer Science, 2002)
Case Based Reasoning has found increasing application on the Internet as a shopping assistant for e-commerce stores. The strength of CBR in this area stems from its reuse of the knowledge base associated with a particular application, thus providing an ideal way to make personalised configuration or technical information available to the Internet user. Since case data may be one aspect of a company's entire knowledge system, it is important to integrate case data easily within a company's IT infrastructure, providing in effect a case-based view on relevant portions of the company knowledge base. We describe CBML, an XML-based Case Mark-Up Language we have developed to facilitate such integration. We will detail the benefits of our system for industry in general in terms of extensibility, ease of reuse and interoperability. The language allows us to make the formal definition of the structure of our cases completely independent of the application code. In this way we allow the structure and definition of our cases to be described and modified easily. Such a language would also allow cases to be exchanged between heterogeneous CBR systems. As an example of how CBML might be used we describe our research on a wireless Case Based assistant for the travel market. In this application user profiles are marked up as sets of cases in CBML.
Keywords: Computer Science